Pengaruh Bioaktivator terhadap Pertumbuhan Sukun (Artocarpus communis Forst) dan Perubahan Sifat Kimia Tanah Gambut - Budi Utomo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
This research was aimed to detect effectiveness of microorganism to increase growth of Artocarpus communis in peat soil. The peat soil came from countryside of Sei Toras, District Panai Tengah, and District Labuhanbatu, North Sumatra Province. Activators tested were Aspergillus sp., EM4, MOD-71, Supernasa and Puja-168. The research was done at Faculty of Agriculture, the University of North Sumatera from February to April 2009. Application of Aspergillus sp. Increased plant height (31.24%), stem diameter (2.84%) and leaf area (63%). Compared to control treatment, the application of Aspergillus sp. increased available P 49%, K 34%, and Ca 45%, however level of total N decreased by 17%.   Keywords: Aspergillus sp., decomposer, nutrient availability, Effective Microorganism, bioactivator